Engage with knowledgeable experts and get accurate answers on IDNLearn.com. Our community is here to provide the comprehensive and accurate answers you need to make informed decisions.

Select the correct answer.

If function [tex]g[/tex] is defined by the equation [tex]y - 3x = -14[/tex], which equation represents the function in function notation?

A. [tex]g(x) = 3x - 14[/tex]
B. [tex]g(x) = -3x - 14[/tex]
C. [tex]g(x) = 3x + 14[/tex]
D. [tex]g(x) = -3x + 14[/tex]


Sagot :

Let's solve the given problem step-by-step.

We are given the equation [tex]\( y - 3x = -14 \)[/tex]. To express this equation in function notation [tex]\( g(x) \)[/tex], we need to solve for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex].

1. Start with the given equation:
[tex]\[ y - 3x = -14 \][/tex]

2. To isolate [tex]\( y \)[/tex], add [tex]\( 3x \)[/tex] to both sides:
[tex]\[ y = 3x - 14 \][/tex]

Now, the equation is in the form [tex]\( y = g(x) \)[/tex], which represents the function in standard function notation.

Thus, we have:
[tex]\[ g(x) = 3x - 14 \][/tex]

Now, let's compare this with the choices given:

A. [tex]\( g(x) = 3x - 14 \)[/tex]

B. [tex]\( g(x) = -3x - 14 \)[/tex]

C. [tex]\( g(x) = 3x + 14 \)[/tex]

D. [tex]\( g(x) = -3x + 14 \)[/tex]

Clearly, the equation [tex]\( g(x) = 3x - 14 \)[/tex] matches option A.

Therefore, the correct answer is:

A. [tex]\( g(x) = 3x - 14 \)[/tex]